Accidents Waiting to Happen: Liability Policy and Toxic Pollution Releases - Alberini, Anna; Austin, David (The Review of Economics and Statistics, 2002)
Proponents of environmental policies based on liability assert that strict liability imposed on polluters induces firms to handle hazardous wastes properly. We examine unintended pollution releases, relating them to the liability imposed on polluters by state mini-Superfund laws. We find that strict liability reduces the frequency and severity of pollution releases, but that its effects vary with firm size. Smaller firms are associated with more pollution releases in states with strict liability, suggesting that in these states smaller firms may have specialized in riskier production processes. Their number, however, has not necessarily grown in response to the state's liability policy.